Cerebral ischemic stroke as demonstration early neurosyphilis - N. G. Komkina; N. V. Nazarenko; T. V. Nazarenko (Бюллетень сибирской медицины)
Specific defeat of vessels of a brain at a syphilis can be one of the stroke reasons. The results of retrospective analysis of 53 case records of patients early manifest by forms neurosyphilis are resulted in article. The first group included the patients who were not receiving specific therapy concerning a syphilis, the patients treated earlier concerning a syphilitic infection have been included in another. From the given groups patients with cerebrovascular forms of neurosyphilis (only 24) have been allocated. The diagnosis has been verified on the basis of the clinical data, results clinic — laboratory and serologikal researches of whey of blood and liquor, the data of a magnito-resonant tomography, dopplerography researches of a brain blood-groove, compression, hypercapnia tests. Features of a clinical current cerebrovascular forms early neurosyphilis with stroke a current are revealed.